Does Part-Time and Intermittent Work during Early Motherhood Lead to Regular Work Later? A comparison of Labor Behavior of Mothers with Young Children in Germany, Britain, The Netherlands and Sweden - Siv S. Gustafsson; Eiko Kenjoh; Cécile Wetzels (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
We use data from Great Britain, Germany, the Netherlands and Sweden to examine whether part-time and intermittent work during early motherhood leads to regular full-time work later. We find that in Sweden, by the time the first child is four years old 80 percent of mothers are working full-time if 25 hours is counted as full-time work, but only 30 percent if a 35-hour threshold is used. This finding contrasts sharply with the work patterns in early motherhood in the other three countries and we interpret itas an effect of woman friendly public policies. Furthermore, while employment of mothers is concentrated in the public sector in all four countries, it is relatively less concentrated there in Sweden. Our results emphasize the importance of labor force transitions of women around the early stages of maternity in explaining cross-sectional findings on women's employment.
Keywords: 330; Weibliche Arbeitskräfte; Mütter; Familienpolitik; Arbeitsmarkt; Teilzeitarbeit; Vergleich; Deutschland; Großbritannien; Niederlande; Schweden